Peran Snouck Hurgronje dalam Merancang Sistem Pendidikan Sekuler di Indonesia dan Dampaknya bagi Kaum Pribumi Islam - Abbas, Irwan; Mahmuddin, Ronny; Hasnidar (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
The secular education system is an education system that separates explicitly between religion and science. Indigenous Indonesians began to recognize the secular education system from the Netherlands at the beginning of the 20th century. Through critical historical methods found: 1) The teachings of jihad in Islam played an important role in encouraging natives to fight in the Netherlands. 2) The teachings of jihad in Islam have made the Netherlands traumatized by indigenous resistance. While the Dutch themselves still want to continue to colonize the natives. 3) How to distance the teachings of Islamic Jihad from the natives is the great homework of Dutch so that the Dutch can still colonize Indonesia? 4) Snouck Hurgronje is a Leiden scientist who managed to provide solutions to the Netherlands. 5) Implementing a secular education system is the solution given by Snouck to the Netherlands. 6) Through the secular education system, the Dutch did succeed in ali.enating the minds of the natives from Islam. 7) The secular education system succeeded in building new beliefs for indigenous children. Their new belief is that the presence of Islam in Indonesia has made Indonesia suffer a setback. 8) They provide a solution, that if the Indonesian people want to achieve progress, then the Indonesian people must ignore religion and focus on developing secular science as the main means of advancing Indonesia in the future.